PELATIHAN GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) PADA PEER EDUCATOR UNTUK MEWUJUDKAN HEALTHY SCHOOL - Andi Selvi Yusnitasari; Marini Amalia Mansur; Framita Rahman; Suci Rahmadani; Andi Tis’a Ramadhani; Handini Damayanti (Gapenas Publisher, 2023)
Schools are one of the potential settings for community empowerment in efforts to implement the Healthy Living Community Movement (Germas). SMA Negeri 7 Takalar is one of the schools in Takalar Regency with 2 (two) priority problems, namely 1) the health service sector, there is no education and routine health screening carried out in schools so that health literacy is low; 2) in the area of availability of health service facilities in schools, there is no information media about health in the school environment and facilities for monitoring student health. Activities carried out to resolve partner problems include peer educator training and empowering academics in schools. This service program runs well and smoothly. This service program, through health education activities and peer educator training that has been carried out, is able to increase the knowledge and skills of students and teachers. It is hoped that all academic members can implement Germas in the school structure so that healthy and intelligent students and a healthy school environment can be created